The TESOL Encyclopedia of English Language Teaching 2019
DOI: 10.1002/9781118784235.eelt0980
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Communicate

Abstract: The act of communicating in a second language has become an important methodological consideration and educational objective in many classrooms around the world. To increase the likelihood that communication will take place, both inside and outside of the classroom, teachers are encouraged to promote students' propensity to engage in communication – known as their “willingness to communicate” (WTC). This entry explains the arguments for developing students' WTC, various factors that play a role in enhancing or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Since the 1980s, encouraging learners' participation through target language use has been a prominent part of second language acquisition (SLA) pedagogy and research. With the advent of communicative approaches to English language teaching, speaking to learn and learning to speak has gained increasing popularity among L2 scholars (Ducker, 2018). Yet, many researchers have confirmed that learners differ in their level of willingness to communicate in L2 (L2 WTC) (Khajavy et al, 2016).…”
mentioning
confidence: 99%
“…Since the 1980s, encouraging learners' participation through target language use has been a prominent part of second language acquisition (SLA) pedagogy and research. With the advent of communicative approaches to English language teaching, speaking to learn and learning to speak has gained increasing popularity among L2 scholars (Ducker, 2018). Yet, many researchers have confirmed that learners differ in their level of willingness to communicate in L2 (L2 WTC) (Khajavy et al, 2016).…”
mentioning
confidence: 99%